Nicotinamide Riboside Vitamin B3 Mitigated C26 Adenocarcinoma–Induced Cancer Cachexia - Park, Jong Min; Han, Young Min; Lee, Ho Jae; Park, Yong Jin; Hahm, Ki Baik (Frontiers in Pharmacology, 2021)
Nicotinamide ribose (NR), vitamin B3, is a substrate for nicotinamide adenine dinucleotide NAD+-consuming enzymes, is a coenzyme for hydride-transfer enzymes including ADP-ribose transferases, poly(ADP-ribose) polymerases, cADP-ribose synthases, and sirtuins, by which it played central role in aging process, neurodegenerative process, and myopathy. Since cancer cachexia is a disease condition presenting with weight loss, skeletal muscle atrophy, and loss of adipose tissue in patients with advanced cancer, we hypothesize NR intake can ameliorate sarcopenia. In this study, we studied whether preemptive administration of NR can ameliorate C26 adenocarcinoma-induced cancer cachexia and explored anti-cachexic mechanisms focused on the changes of muscle atrophy, cachexic inflammation, and catabolic catastrophe. Dietary intake of NR containing pellet diet significantly attenuated cancer cachexia in mice model. Started with significant inhibition of cachexic factors, TNF-alpha and IL-6, NR afforded significant inhibition of either muscle specific ubiquitin-proteasome ligase such as atrogin-1 and MuRF-1 or mitofusin-2 and PCG-1alpha. Significant inhibition of epididymal fat lipolysis was noted with significant inhibition of responsible ATAL gene. Furthermore, NR administration significantly increased crucial enzyme in the biosynthesis of NAD+, nicotiamide phosphoribosyltransferase (NAMPT), while NR significant inhibited NAD+ sensitive deacetylase, SIRT1. Preemptive intake of NR in patients vulnerable to cachexia can be an anticipating option to ameliorate cancer cachexia.